Simulation of magnetophoretic blood cells sorter platform - Foughalia, Aissa; Ibrahim, Siti Noorjannah; Khan, Sheroz (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
Analysis of cells is important for medical research and pharmaceuticalindustry. This paper presents a new technique for sorting blood cellson a bio-analysis platform that combines the magnetophoretic force andhydrodynamic force as the means of cell manipulation. The integra-tion of these two techniques can improve on-chip sorting ability whichcould result in high throughput compared to microfluidic system thatuses hydrodynamic method alone. Here, studies on the magnetic densitythat profiled the actual magnetophoretic force and the hydrodynamicforce analysis were conducted using COMSOL Multiphysics v4.2 soft-ware. These simulations are important in order to assess magnetophore-sis performance during experiments. The suggested model is capable ofseparating target cells from a heterogeneous population which can be ap-plied for detection purpose particularly in cell biology, immunology, stemcell research, and other clinical applications.